Ab initio calculation of the evolution of [SiN4‐nOn] tetrahedron during β‐Si3N4(0001) surface oxidation. Issue 4 (2nd December 2019) - Cai, Jianpeng; Hou, Xinmei; Fang, Zhi; Wang, Enhui; Feng, Jiao; Chen, Junhong; Liang, Tongxiang; Bei, Guoping
Abstract: The easy‐going oxidation of silicon nitride (Si3 N4 ) at high temperature greatly hampers its potential applications. Here, we explored the reaction mechanism between β ‐Si3 N4 and O2 via density functional theory (DFT) calculation, which discloses that O atoms are preferentially adsorbed on the top of Si atoms and N2 starts to be generated as the dominant gas product at 2/3 monolayer (ML) O coverage. The vacancies formed by N2 removal attract the O adatoms to transfer to the site of the N vacancy, which accelerates the adsorption of O and the formation of Si–O bonds toward the growth of SiO2 product. The surface oxidation of β ‐Si3 N4 (0001) has been clarified by the unambiguous evolution of [SiN4 ‐n O n ] (n = 0‐4) tetrahedrons going through from [SiN4 ] tetrahedron to [SiO4 ] tetrahedron, providing a deep insight into intrinsic oxidation process of Si3 N4 ceramic. Abstract : The vacancies formed by N2 removal attract O adatoms to transfer to the N vacancy site, which accelerates the oxidation process. The surface oxidation of β‐Si3N4 (0001) has been clarified by the unambiguous evolution of [SiN4‐n On ] (n = 0‐4) tetrahedrons going through from [SiN4 ] to [SiO4 ] tetrahedron.